Uav Icing Trials: A New Approach - Franzetti, I.D.D.M.P.; Avi, A.; Capello, E.; Quaranta, G.; Parin, R. (My University, 2024)
The experimental analysis of ice formation on multirotor propellers is proposed in this work. The effect of cloud droplet size and liquid water content is tested at different temperature conditions to examine the ice structure formation. Single rotor experiments have been conducted for 10"x4.7" and 15"x5" propellers at -2º C and -12º C making use of an icing wind tunnel inside a climatic chamber for the simulation of realistic icing conditions. A force-torque sensor is used for the performance evaluation of the propellers in terms of thrust and torque during the ice accretion. The objective of this work is the characterization of the ice formation based on cloud characteristics together with the study of the ice shedding phenomenon that entails abrupt performance changes. The resulting experimental data can be used as a reference for thrust loss estimation and required power computation aimed at planning real-life UAV missions in alpine environments.